2011
DOI: 10.2109/jcersj2.119.667
|View full text |Cite
|
Sign up to set email alerts
|

Texture development of surface-modified SiC prepared by EPD in a strong magnetic field

Abstract: Silicon carbide is a very important material for various applications and its properties are expected to be improved by controlling the crystallographic orientation. It was difficult to simultaneously consolidate SiC powder and sintering additives by electrophoretic deposition (EPD) because of the different electrophoretic mobility. When using the alumina-coated SiC by the solgel method, it is possible to deposit SiC and sintering additives by EPD at the same time.In this study, we demonstrated that the c-axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This process has several advantages such as: short depositing time, simple equipment requirement, and little restriction of substrate shape, making it become a cost-effective and versatile process [ 7 , 8 ]. The EPD process has been reported as a widely used technique for preparing a variety of the deposits including coatings [ 9 11 ] and ceramic bodies [ 12 14 ]. In particular, the EPD process has also been utilized to fabricate the phosphor deposits for the pseudo-white LEDs [ 15 18 ], even the monochromatic and color screens for the information displays [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process has several advantages such as: short depositing time, simple equipment requirement, and little restriction of substrate shape, making it become a cost-effective and versatile process [ 7 , 8 ]. The EPD process has been reported as a widely used technique for preparing a variety of the deposits including coatings [ 9 11 ] and ceramic bodies [ 12 14 ]. In particular, the EPD process has also been utilized to fabricate the phosphor deposits for the pseudo-white LEDs [ 15 18 ], even the monochromatic and color screens for the information displays [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this background, we found that a strong magnetic field has been successfully utilized to control the development of texture, even for diamagnetic Al 2 O 3 , by colloidal processing for particle dispersion in a slurry . Magnetic orientation has been applied to a wide variety of useful ceramics with feeble magnetic susceptibilities, such as TiO 2 , ZnO, AlN, SiC, zeolite, piezoelectric ceramics, etc …”
Section: Introductionmentioning
confidence: 99%